Beetles as biodiversity indicators at different elevations in Fraser’s hill, Malaysia - Muneeb M. Musthafa,; Fauziah Abdullah, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Malaysia is described as one of the twelve mega-store of biological diversity in the world however, very little is known about the forest reserves and their beetle diversity in relation to elevation. Two elevations ranging from 500 to 600 m and 1000 to 1100 m were selected for sampling with light traps, malaise traps and pitfall traps. Altogether 222 individuals were collected from 23 families from these two elevation clines. Oxyletus lucidulus Cam is the dominant species found at lower elevation. While Chlaenius species showed dominance at higher elevation gradient at Fraser’s hill. The overall result shows that, lower elevation range (500-600 m) showed lower abundance (Margalef Index; 7.217), diversity (Shannon-Weaner Index; 2.546) and Evenness Index; 0.510 while higher lavational range (1000-1100 m) showed slightly higher values for all. Not suitable in abstract. This study can be utilized to evaluate the suitability of selected beetle species diversity as a possible biodiversity indicator at Fraser’s hill.